(untitled) (Mora, 2014)
En la obra poética de Marosa di Giorgio, el erotismo se asocia a una concepción ominosa de la maternidad. De un modo radical, esta escritura subvierte la figura judeocristiana de la madre pura y beata para postular esa “maternidad monstruosa” como apología del acto creativo. En la profusa red de herencias surrealistas y afinidades electivas que rodean esta poética, hay al menos tres escritoras rioplatenses a las que puede identificarse como precursoras: Delmira Agustini, Armonía Somers y Alejandra Pizarnik. Abstract In the poetry of Marosa di Giorgio, eroticism is associated with a conception of motherhood quite ominous. In a radical way, this script subverts Judeo-Christian figure of pure and pious mother to postulate this “monstrous maternity” in defence of the creative act. In the profuse network of surrealist legacies and elective affinities surrounding this poetic, there are at least three writers in Rio de la Plata to wich can be identified as precursors: Delmira Agustini, Armonia Somers and Alejandra Pizarnik.